Lithium ion battery and electric device
By optimizing the formulation and structure of the lithium-ion battery electrolyte, the thermal stability and side reaction problems of the electrolyte under high-rate charging and discharging and high-temperature conditions are solved, and the battery's high energy density, long cycle performance and safety of use are achieved. .
Patent Information
- Application Number
- CN202411731815.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-11
AI Technical Summary
In the high-rate charging and discharging and high-temperature conditions, the electrolyte has poor thermal stability, resulting in frequent side reactions and damages the battery's cycle life and safety performance.
By optimizing the electrolyte formulation, control the content of LiPF6, fluorovinyl carbonate, vinylene carbonate, lithium difluorophosphate and cyano-containing nitrile organic compounds to ensure the weight percentage of nitrile organic compounds and lithium difluorophosphate. The total is between 1 wt% and 2 wt%, and the Fourier transform infrared spectroscopy test is carried out to satisfy the specific characteristic absorption peak intensity ratio and inhibit the side reaction of the electrolyte.
While maintaining high energy density, it improves the long cycle performance and safety of lithium-ion batteries under high magnification and high temperature operating conditions, extends the cycle life of the battery and reduces heating.
Smart Images

Figure CN119419335A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrical devices, and in particular to a lithium-ion battery and an electrical device. Background Art
[0002] Lithium-ion batteries play a vital role in portable devices, electric vehicles and renewable energy storage systems due to their excellent energy storage capacity and wide range of applications. However, as application demand grows, the performance requirements for lithium-ion batteries are also getting higher and higher, such as maintaining high energy density and high-rate charge and discharge capabilities while achieving longer cycle life and greater safety.
[0003] In the existing lithium-ion battery electrolyte system, lithium hexafluorophosphate (LiPF 6 ) is the most commonly used electrolyte lithium salt, LiPF 6 It has high ionic conductivity and acts as a medium for transmitting ions in the electrolyte, giving the battery better charge and discharge performance.
[0004] In actual application, due to the existence of internal resistance, the battery will generate significant Joule heat under high-rate charge and discharge conditions, and the internal temperature of the battery will also rise. High temperature will cause electrolytes such as LiPF 6 The thermal stability of lithium salts or additives is poor, which may cause thermal decomposition or aggravate the side reactions of lithium salts and additives on the surface of positive and negative electrode materials. 6 For example, LiPF 6 A side reaction occurs, producing free anion PF 6 - These highly corrosive byproducts will further corrode the battery shell and the CEI film (Cathode Electrolyte Interphase, a passivation film formed when the positive electrode material and the electrolyte are in contact in lithium-ion batteries) and SEI film (Solid Electrolyte Interface, a passivation layer covering the surface of the negative electrode material formed during the first charge and discharge process of lithium-ion batteries) on the surface of the positive and negative electrode materials, forming a chain reaction that continuously damages the battery safety performance.
[0005] On the other hand, highly corrosive by-products will also lead to the inactivation of energy storage substances in the positive and negative electrode materials, causing a rapid decrease in battery capacity, making it difficult to ensure the battery's cycle life; and the deposition of side reaction products will further increase the impedance of the battery system, aggravate the heating of the battery, and further reduce the release rate of the battery's internal energy. Summary of the invention
[0006] In order to solve the above problems, the thermal stability of the electrolyte is improved, and its side reactions are inhibited, so that the battery can maintain high energy density while improving the long cycle performance and safety of use under high rate and high temperature conditions. The first aspect of the present application provides a lithium-ion battery, including a shell, a winding core assembled in the shell, and an electrolyte injected into the shell to infiltrate the winding core, the winding core includes a stacked positive electrode sheet, a separator and a negative electrode sheet, the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer coated on at least one surface of the positive electrode collector, the negative electrode sheet includes a negative electrode collector and a negative electrode active material layer coated on at least one surface of the negative electrode collector, and the electrolyte includes: 12wt%-18wt% LiPF 6 , 3wt%-8wt% of fluoroethylene carbonate, 0.1wt%-0.5wt% of vinylene carbonate, 0.5wt%-1.5wt% of lithium difluorophosphate and 0.4wt%-0.8wt% of a cyano-containing nitrile organic compound, and the balance is a solvent; wherein the total weight percentage of the nitrile organic compound and the lithium difluorophosphate should be 1wt%-2wt%, and after Fourier transform infrared spectroscopy testing, it meets the following requirements:
[0007] 5%≤I A / I B ≤25% and 25%≤I C / I D ≤50%
[0008] Among them I A and I B They are 875-885cm in the infrared spectrum. -1 Wave number and 835~845cm -1 The intensity of the characteristic absorption peak centered at the wave number; I C and I D The infrared spectrum is 725-735 cm -1 Wave number and 710~720cm -1 The intensity of the characteristic absorption peak centered at wavenumber.
[0009] By controlling the contents of fluorine-containing additives, lithium salts and cyanide-containing nitrile organic compounds in the electrolyte, which are chemically active and prone to side reactions and have poor thermal stability, within specific ranges, the long cycle performance and safety performance under high rate and high temperature conditions are improved while maintaining the high energy density of the lithium-ion battery. In addition, the electrolyte is characterized by Fourier transform infrared spectroscopy, and the intensities are I A ,I B ,I C and I D Four characteristic absorption peaks, agreed to be 5% ≤ I A / I B≤25% and 25%≤I C / I D ≤50%, reflecting the degree of inhibition of the electrolyte on side reactions, fully ensuring the thermal stability of the electrolyte in the electrochemical environment.
[0010] In some optional embodiments, the positive electrode sheet is a low-residual alkali positive electrode sheet that has been washed with water, and the electrolyte needs to be discharged to the discharge cut-off voltage at least once before the Fourier transform infrared spectroscopy test is performed. The washed low-residual alkali positive electrode sheet can improve both the high potential life and low-temperature output characteristics of the lithium-ion battery. The electrolyte of the battery that has been discharged at least once is closer to the electrolyte state in actual application. The results of the infrared spectrum test can also more accurately reflect the changes in the electrolyte after the electrochemical reaction and judge the degree of side reactions.
[0011] In some optional embodiments, the Fourier transform infrared spectroscopy test comprises the following steps:
[0012] S11: Take one of the lithium-ion batteries and let it stand at 25° C. for 4 hours;
[0013] S12: discharging the lithium-ion battery at a discharge rate less than or equal to 0.2C until the cut-off voltage is reached, and leaving the battery to stand for 30 minutes;
[0014] S13: disassembling the lithium-ion battery and extracting the electrolyte by centrifugation; and
[0015] S14: The electrolyte is transferred to a closed liquid pool and then sent to a Fourier transform infrared spectrometer for testing. The infrared absorption spectrum wavelength range is set to: 400 cm -1 -4000cm -1 , scan to obtain an infrared spectrum containing several characteristic absorption peaks.
[0016] In some optional embodiments, the conductivity of the electrolyte at 25° C. is greater than or equal to 10 mS / cm, and the lithium ion migration number is greater than or equal to 0.4. The conductivity of the electrolyte is constrained to ensure the transmission efficiency of the electrolyte to charged particles, and the lithium ion migration number is constrained to ensure that the charge transfer in the electrolyte is mainly contributed by lithium ions, which helps to improve the coulomb efficiency and energy efficiency of the battery, reduce the polarization phenomenon during the charge and discharge process, and thus improve the cycle stability and service life of the battery.
[0017] In some alternative embodiments, the lithium-ion battery is charged at a rate of 0.1C at 25°C. When the charging voltage reaches the range of 4.45V - 4.78V, the material specific capacity of the positive electrode active material layer is E mAh / g, and 5 ≤ E ≤ 20. By defining that the positive electrode active material layer still maintains a relatively high specific capacity under the high-potential condition of 4.45V - 4.78V, the stability of the electrochemical system during high-potential charging of the battery is ensured. Also, due to the positive correlation between the specific capacity of the positive electrode active material layer and the battery discharge performance, the discharge rate performance and discharge stability of the battery are estimated simultaneously, ensuring the high energy density and high rate performance of the battery that meets this defined condition.
[0018] In some alternative embodiments, after the lithium-ion battery has completed 100 charge-discharge cycles, the thickness of the fluorine-containing layer on the surface of the positive electrode active material layer is measured to be d microns. Micro-area elemental analysis is performed using DES energy spectrum. The proportion of fluorine element on the surface of the negative electrode active material layer in all elements is x%, satisfying: 0 < d / x < 0.1. By restricting the thickness of the fluorine-containing layer on the surface of the positive electrode active material layer and the proportion of fluorine element on the surface of the negative electrode active material layer, the density and mechanical strength of the fluorine-containing deposition layer (i.e., the CEI film of the positive electrode and the SEI film of the negative electrode) are reflected, optimizing the chemical stability of the interfaces between the positive and negative electrode sheets and the electrolyte, thereby suppressing side reactions of the electrolyte and improving the high-temperature cycle performance and safety performance of the battery during high-rate charge and discharge.
[0019] In some alternative embodiments, the solvent includes one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, and the nitrile organic compound is succinonitrile and / or 1,3,6-hexanetricarbonitrile. Using the above solvents can meet the requirements of lithium salt dissolution and ion mobility and conductivity, and at the same time assist in forming a stable SEI film on the surface of the negative electrode sheet, enhancing the stability of the chemical system inside the battery and extending the service life; the nitrile organic compound is selected as succinonitrile and / or 1,3,6-hexanetricarbonitrile, which can improve the specific capacity and first charge-discharge efficiency of the battery, and at the same time broaden the electrochemical stability window of the electrolyte, thereby enhancing the thermal stability and cycle performance of the electrolyte. On the other hand, it can further assist in the formation of a stable SEI film and inhibit the decomposition of the electrolyte on the negative electrode sheet.
[0020] In some alternative embodiments, the positive electrode active material layer includes a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent, and the positive electrode active material is a metal oxide formed by the combination of one or more metal elements among cobalt, manganese, aluminum, and nickel and lithium. Utilizing the high specific capacity characteristics of cobalt, manganese, aluminum, and nickel elements, the formation of metal oxides by combining with lithium atoms can significantly improve the energy density of the battery and expand the upper limit of the battery charge-discharge rate.
[0021] In some optional embodiments, the negative electrode active material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material includes one or more of artificial graphite, natural graphite, silicon-oxygen material, and silicon-carbon material, and the mass proportion of silicon in the negative electrode active material is 0%-22%. By controlling the mass proportion of silicon in the negative electrode active material, on the one hand, silicon-based materials have a higher gram capacity than carbon-based materials, which can reduce the density and thickness of the negative electrode active material layer and improve the dynamic performance and energy storage capacity of the battery charge and discharge process; on the other hand, controlling the silicon content to 0%-22% can inhibit the volume expansion due to alloying of silicon and lithium, maintain the structural stability of the negative electrode active material layer, and thus ensure the cycle performance and safety of the battery.
[0022] In some optional embodiments, the positive electrode active material is lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, and the ratio of the number of nickel atoms in the positive electrode active material to the total number of transition metal atoms is greater than or equal to 79%. By controlling the ratio of the number of nickel atoms in the positive electrode active material to the total number of transition metal atoms, the electron conductivity and ion diffusion in the coil core are enhanced, the energy density of the battery charge and discharge process is improved, and high-rate charge and discharge are achieved.
[0023] In some optional embodiments, the positive electrode collector also reserves a positive electrode empty foil area that is not covered by the positive electrode active material layer, and the positive electrode empty foil area accounts for 1.8%-12.5% of the surface area of the positive electrode collector; the negative electrode collector also reserves a negative electrode empty foil area that is not covered by the negative electrode active material layer, and the negative electrode empty foil area accounts for 1.5%-12% of the surface area of the negative electrode collector. By reserving an empty foil area on the positive electrode collector and the negative electrode collector to be rolled and flattened for use as a full-ear structure, the internal resistance of the battery is reduced, the heat generation of the battery under high-rate conditions is reduced, and the area of the empty foil area on the positive electrode sheet and the negative electrode sheet is limited, which not only ensures that the positive and negative electrodes of the winding core are smoothly electrically connected to the external electrodes of the battery, but also avoids an excessively high proportion of the empty foil area, which increases the weight and volume of non-energy storage materials and affects the weight energy density and volume energy density of the battery.
[0024] In some optional embodiments, at least one edge of the positive electrode active material layer is coated with an inorganic ceramic coating, and the width of the inorganic ceramic coating is 1.1%-6.5% of the width of the positive electrode sheet. The inorganic ceramic coating acts as a barrier to prevent the uncontrollable propagation of heat and current when the battery is in abnormal conditions, such as overcharge, overdischarge, short circuit, etc., and reduce the risk of thermal runaway; if the width of the inorganic ceramic coating is too wide, the width of the active material layer of the positive electrode sheet will be reduced, thereby reducing the energy capacity of the core. Limiting the width of the inorganic ceramic coating to 1.1%-6.5% of the width of the positive electrode sheet can not only improve the safety of the battery, but also minimize the impact on the battery capacity.
[0025] In some optional embodiments, the inorganic material particles forming the inorganic ceramic coating include one or more of aluminum oxide, manganese dioxide, magnesium oxide, silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, iron oxide, boehmite, gypsum, talc, and calcite, and the average particle size Dv50 of the inorganic material particles is 0.5-7.5 microns. The inorganic ceramic coating made of the above-mentioned inorganic material particles has good thermal stability, remains electrically insulating in a high temperature environment, provides mechanical support for the positive electrode active material layer, and enhances the structural stability of the positive electrode sheet. The average particle size Dv50 of the inorganic material particles is 0.5-7.5 microns, which can form a more uniform coating, reduce coating pore defects, and has good coating quality and electrical insulation performance, which helps to improve the safety of the battery.
[0026] The second aspect of the present application provides an electrical device, including a controller, a motor connected to and controlled by the controller, and a battery for powering the controller, wherein the battery is a lithium-ion battery according to any one of the above items. Since lithium-ion batteries have the above-mentioned beneficial effects, the electrical device provided by the present application has a more stable electrolyte system during high-power charging and discharging, can suppress the occurrence of thermal decomposition and side reactions, and is safer to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 is a schematic structural diagram of a lithium-ion battery of an optional embodiment of the present application;
[0029] Figure 2 This is a schematic structural diagram of a lithium-ion battery roll core according to an optional embodiment of the present application;
[0030] Figure 3 This is a front view of a positive electrode sheet of a lithium-ion battery of an optional embodiment of the present application;
[0031] Figure 4 is a front view of a negative electrode sheet of a lithium-ion battery according to an optional embodiment of the present application;
[0032] Figure 5 It is a schematic diagram of the structure of an electrical device of an optional embodiment of the present application.
[0033] Figure markings: 1-lithium-ion battery, 2-controller, 3-motor, 10-housing, 12-winding core, 13-electrolyte, 121-positive electrode sheet, 123-diaphragm, 125-negative electrode sheet, 1210-positive electrode active material layer, 1211-positive electrode current collector, 1212-positive electrode empty foil area, 1214-inorganic ceramic coating, 1250-negative electrode active material layer, 1251-negative electrode current collector, 1252-negative electrode empty foil area. DETAILED DESCRIPTION
[0034] Embodiments of the present embodiment are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present embodiment, and should not be construed as limiting the present embodiment.
[0035] In the description of this embodiment, it should be understood that descriptions involving orientation, such as up, down, front, back, left, right, etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing this embodiment and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on this embodiment.
[0036] In the description of this embodiment, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0037] In the description of this embodiment, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in this embodiment based on the specific content of the technical solution.
[0038] Please refer to Figure 1-Figure 2 , Figure 1 The figure shows a schematic diagram of the structure of a lithium-ion battery after assembly according to an embodiment of the present application. Figure 2 A schematic structural diagram of a winding core is shown.
[0039] The method for preparing the lithium-ion battery 1 mentioned in the present application comprises the following steps:
[0040] S21: Prepare positive electrode sheet 121: Weigh 97.3% lithium nickel cobalt manganese oxide (chemical formula: LiNi 0.8Co 0.1 Mn 0.1 O 2 , also known as 811 positive electrode), 0.4% carbon nanotubes, 1.2% conductive carbon black, and 1.1% polyvinylidene fluoride as the solid matter of the positive electrode slurry, the solid matter of the positive electrode slurry is dispersed in N-methyl-2-pyrrolidone, the solid content is 60%, after mixing in a homogenizer, coated on both sides of the aluminum foil, and dried to obtain a positive electrode sheet 121;
[0041] S22: preparing the negative electrode sheet 125: weighing 92% artificial graphite, 4% silicon oxide material, 1% acetylene black, 1% carboxymethyl cellulose, and 2% polyacrylic acid as solid substances of the negative electrode slurry according to weight percentage, dispersing the solid substances of the negative electrode slurry in deionized water with a solid content of 40%, mixing in a homogenizer, coating on both sides of the copper foil, and drying to obtain the negative electrode sheet 125;
[0042] S23: preparing the winding core 12: rolling the positive electrode sheet 121 and the negative electrode sheet 125 respectively, cutting and die-cutting them according to the size requirements, and winding them together with the separator 123 to obtain the winding core 12;
[0043] S24: preparing electrolyte 13: mixing ethylene carbonate, diethyl carbonate and ethyl acetate in a mass ratio of 1:3:1 to obtain an organic solvent, dissolving lithium salt and additives in the mixed organic solvent to prepare electrolyte 13, wherein the specific proportions of the components in the electrolyte 13 are 14wt% lithium hexafluorophosphate, 6wt% fluoroethylene carbonate, 15wt% ethylene carbonate, 48wt% dimethyl carbonate, 15wt% ethyl acetate, 0.5wt% vinylene carbonate, 1wt% lithium difluorophosphate and 0.5wt% succinonitrile.
[0044] S25: Assembling the battery: After welding the pole ears of the battery core 12 to the electrical connecting piece, the battery core 12 is placed in a steel shell, and the electrolyte 13 is injected. The battery is sealed and formed to obtain a battery.
[0045] It can be understood that the above-mentioned aluminum foil is the positive electrode current collector 1211, carbon nanotubes and conductive carbon black are positive electrode conductive agents, polyvinylidene fluoride is the positive electrode binder, copper foil is the negative electrode current collector 1251, acetylene black is the negative electrode conductive agent, polyacrylic acid is the negative electrode binder, carboxymethyl cellulose is used as a dispersant, and the steel shell is the battery shell 10. The above example is a manufacturing method for cylindrical batteries, which is also applicable to square batteries.
[0046] The present application provides a lithium-ion battery 1, comprising a housing 10, a winding core 12 assembled in the housing 10, and an electrolyte 13 injected into the housing 10 to soak the winding core 12, wherein the electrolyte 13 comprises: 12 wt%-18 wt% LiPF 6, 3wt%-8wt% of fluoroethylene carbonate, 0.1wt%-0.5wt% of vinylene carbonate, 0.5wt%-1.5wt% of lithium difluorophosphate and 0.4wt%-0.8wt% of cyanide-containing nitrile organic compounds, and the balance is solvent; wherein the total weight percentage of the nitrile organic compounds and the lithium difluorophosphate should be 1wt%-2wt%.
[0047] By optimizing the electrolyte 13 ratio, especially controlling the addition ratio of fluorine-containing additives, lithium salts and cyanide-containing nitrile organic compounds, which are chemically active, prone to side reactions and have poor thermal stability, within a specific range, and combining them with a washed low-residual alkali positive electrode sheet 121, the solvent molecules and PF can be improved without reducing the conductivity. 6 - Combined with the proportion of lithium ions, the number of free anions in the electrolyte 13 is reduced, the corrosion of the electrolyte 13 system to the shell 10 (steel shell) is reduced, and the safety of the battery is ensured. The fluorine-containing additive in the electrolyte 13 preferentially deposits a dense fluorine-containing passivation layer on the surface of the positive electrode sheet 121 and the negative electrode sheet 125, thereby improving the electrochemical stability of the interface between the electrolyte 13 and the positive / negative electrode sheet 125, thereby improving the high-temperature cycle performance and safety performance of the battery at high-rate charge and discharge.
[0048] Furthermore, the prepared electrolyte 13 needs to be further characterized by scientific instruments to monitor the content of side reaction products that are destructive to the electrochemical system of the battery generated in the mixed electrolyte 13 system. It can be understood that the characterized electrolyte 13 system is preferably an electrolyte 13 that has been discharged to a discharge cut-off voltage at least once. It can be understood that different batteries have different cut-off voltages. The discharge cut-off voltage of a lithium-ion battery of a ternary positive electrode material type is generally 2.5V. When the battery is discharged to the discharge cut-off voltage, it no longer outputs current to the outside. The electrolyte 13 undergoes a discharge transfer lithium ion electrochemical action, and then undergoes a Fourier transform infrared spectroscopy test, which can relatively accurately reflect the degree of side reactions that occur when the electrolyte 13 participates in the electrode reaction.
[0049] Specifically, the present application uses a Fourier transform infrared spectrometer to analyze the composition of the electrolyte 13, and the Fourier transform infrared spectrum test includes the following steps:
[0050] S11: Take one of the lithium-ion batteries 1 and let it stand at 25° C. for 4 hours;
[0051] S12: discharging the lithium-ion battery 1 at a discharge rate less than or equal to 0.2C until the cut-off voltage is reached, and then leaving the battery to stand for 30 minutes;
[0052] S13: disassembling the lithium-ion battery 1 and extracting the electrolyte 13 by centrifugation; and
[0053] S14: The electrolyte 13 is transferred to a closed liquid pool and then sent to a Fourier transform infrared spectrometer for testing. The infrared absorption spectrum wavelength range is set to 400 cm -1 -4000cm -1 , scan to obtain an infrared spectrum containing several characteristic absorption peaks.
[0054] The infrared spectrum was separated by Voigt contour line using relevant software, and the peaks at 875-885 cm -1 Wave number and 835~845cm -1 The characteristic absorption peaks A and B centered at the wave number, and the characteristic absorption peaks at 725-735 cm -1 Wave number and 710~720cm -1 The characteristic absorption peak C and characteristic absorption peak D centered on the wave number, the intensity of each characteristic absorption peak is calculated as follows: A ,I B ,I C and I D , and meet: 5% ≤ I A / I B ≤25% and 25%≤I C / I D ≤50%. Effectively control the free anion content in the electrolyte 13 system, PF 6 - The high ratio of bonding with lithium ions can inhibit the side reactions of the electrolyte 13 and fully ensure the thermal stability of the electrolyte 13 in the electrochemical environment.
[0055] Through the above tests, the side reaction degree of electrolyte 13 can be basically understood. Furthermore, the efficiency of electrolyte 13 in transmitting lithium ions can be verified from the conductivity and lithium ion migration number of electrolyte 13 to ensure the high rate charge and discharge performance of the battery. Among them, the conductivity of electrolyte 13 at 25°C is greater than or equal to 10mS / cm, and the lithium ion migration number is greater than or equal to 0.4. High conductivity ensures the transmission efficiency of electrolyte 13 for charged particles, and high lithium ion migration number ensures that the charge transmission in electrolyte 13 is mainly contributed by lithium ions, which helps to improve the coulomb efficiency and energy efficiency of the battery, reduce polarization during charging and discharging, and thus improve the cycle stability and service life of the battery.
[0056] In some alternative embodiments, the ionic transport performance of the electrolyte 13 system can also be improved by selecting appropriate solvent types and nitrile compounds. The solvents include one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. The nitrile organic compound is succinonitrile and / or 1,3,6-hexanetricarbonitrile. Using the above solvents can meet the requirements for the dissolution of lithium salts and the ion mobility and conductivity, and at the same time is conducive to the formation of a stable SEI film on the surface of the negative electrode sheet 125 by the fluorine-containing lithium intercalation group, improving the stability of the electrochemical system in the battery and extending the service life. The nitrile organic compound is selected as succinonitrile and / or 1,3,6-hexanetricarbonitrile, which can improve the specific capacity and the first charge-discharge efficiency of the battery, and at the same time broaden the electrochemical stability window of the electrolyte 13, thereby improving the thermal stability and cycling performance of the electrolyte 13. On the other hand, it can further assist in the formation of a stable SEI film and inhibit the side reactions at the interface between the electrolyte 13 and the negative electrode sheet 125.
[0057] In addition to the above improvements corresponding to the electrolyte 13 system and the determination of performance parameter indicators, the present application also proposes an optimization scheme for the structure of solid materials in the battery system. One specific optimization scheme is as follows: The lithium-ion battery 1 is charged at a rate of 0.1C at 25°C. When the battery voltage reaches the range of 4.45V - 4.78V during charging, the material specific capacity of the positive electrode active material layer 1210 is set to E mAh / g, and 5 ≤ E ≤ 20 is satisfied. By limiting the battery to operate at a high potential in the range of 4.45V - 4.78V, the positive electrode active material layer 1210 still maintains a relatively high specific capacity, ensuring the stability of the electrochemical system during high-potential charging of the battery. Also, because of the positive correlation between the specific capacity of the positive electrode active material layer 1210 and the discharge performance of the battery, the discharge rate performance and discharge stability of the battery are estimated, ensuring the high energy density and high rate performance of the battery that meets this limiting condition.
[0058] In another alternative embodiment, after the lithium-ion battery 1 has completed 100 charge-discharge cycles, the thickness of the fluorine-containing layer on the surface of the positive electrode active material layer 1210 is measured to be d microns, and the proportion of the fluorine element content in all elements on the surface of the negative electrode active material layer 1250 is x%, satisfying: 0 < d / x < 0.1. The thickness of the fluorine-containing layer on the surface of the positive electrode active material layer is obtained by observing and measuring the cross-section CP of the positive electrode sheet using a SEM scanning electron microscope. The elemental analysis of the negative electrode active material layer 1250 is performed by micro-area elemental analysis using an EDS energy spectrum. The EDS distinguishes various elements contained in the negative electrode active material by detecting the X-rays generated when the electron beam interacts with the negative electrode active material sample, and calculates the relative content of each element. The content of the fluorine element is denoted as x.
[0059] By monitoring the structural changes on the surfaces of the positive and negative active materials, the thickness d of the fluorine-containing layer on the surface of the positive active material layer 1210 and the proportion x of the fluorine element content on the surface of the negative active material layer 1250 are made to satisfy 0 < d / x < 0.1, enhancing the density and mechanical strength of the fluoride-containing protective layers formed on the surfaces of the positive electrode sheet 121 and the negative electrode sheet 125 (i.e., the CEI film formed on the positive electrode surface and the SEI film formed on the negative electrode surface), optimizing the chemical stability of the interfaces between the positive electrode sheet 121, the negative electrode sheet 125 and the electrolyte 13, thereby suppressing the interfacial side reactions of the electrolyte 13, ensuring the cycle life of the battery, and improving the safety performance of the battery.
[0060] Furthermore, the internal resistance of the battery can also be reduced by improving the material systems and structural designs of the positive electrode sheet 121 and the negative electrode sheet 125, reducing the heat generation during battery operation to inhibit the thermal decomposition of the electrolyte 13; and enhancing the energy storage performance of the electrodes to increase the upper limit of the charge-discharge rate of the battery.
[0061] In some alternative embodiments, the positive active material in the positive active material layer 1210 is selected as a metal oxide formed by the combination of one or more metal elements including cobalt, manganese, aluminum and nickel with lithium, preferably: lithium nickel cobalt manganate or lithium nickel cobalt aluminate, wherein the proportion of the number of nickel atoms in the total number of transition metal atoms is greater than or equal to 79%. Effectively enhancing the electron conductivity and ion diffusivity within the winding core 12, increasing the energy density during the charge-discharge process of the battery, and achieving high-rate charge and discharge.
[0062] In some alternative embodiments, the negative active material in the negative active material layer 1250 is selected from one or more of artificial graphite, natural graphite, silicon-oxygen materials, and silicon-carbon materials, and the mass proportion of silicon element in the negative active material is 0% - 22%. Further, the mass proportion of silicon element in the negative active material is 3.5% - 22%. By controlling the mass proportion of silicon element in the negative active material, the energy storage capacity of the battery is balanced with the insecurity caused by the volume expansion during the alloying of silicon and lithium, thereby ensuring the large-capacity energy storage and safety of the battery.
[0063] Among them, a common silicon-carbon material is formed by carbon coating elemental silicon. By coating amorphous carbon and / or carbon nanotubes on the surface of elemental silicon, the interfacial stability and conductivity of elemental silicon can be improved, the film-forming integrity of the SEI film can be enhanced, and the cycle and safety performance of the battery can be improved.
[0064] Carbon-based materials can be a mixture of one or more of artificial graphite, natural graphite, hard carbon, and soft carbon. Artificial graphite refers to graphite materials manufactured by artificial synthesis methods, such as obtained by high temperature and high pressure treatment of carbon materials (such as graphite ore, coke, etc.) or chemical synthesis methods. It has strong consistency in morphology and particle size distribution, and the structure can be in various forms, such as block, fiber or powder; natural graphite refers to graphite formed naturally in nature, mainly in the form of ores such as graphite schist, graphite gneiss, graphite-containing schist and metamorphic shale; hard carbon refers to carbon that is difficult to graphitize, which is usually obtained by thermal decomposition of polymers, such as resin carbon, organic polymer pyrolytic carbon and carbon black; soft carbon refers to easily graphitized carbon, that is, amorphous carbon that can be graphitized at high temperatures above 2500°C. Common soft carbons include petroleum coke, needle coke, carbon fiber, carbon microspheres, etc.
[0065] In some optional embodiments, see Figure 3-Figure 4 The positive electrode current collector 1211 also reserves a positive electrode empty foil area 1212 that is not covered by the positive electrode active material layer 1210, and the positive electrode empty foil area 1212 accounts for 1.8%-12.5% of the surface area of the positive electrode current collector 1211; the negative electrode current collector 1251 also reserves a negative electrode empty foil area 1252 that is not covered by the negative electrode active material layer 1250, and the negative electrode empty foil area 1252 accounts for 1.5%-12% of the surface area of the negative electrode current collector 1251. The empty foil area is used to form a full-pole ear, which can greatly reduce the internal resistance of the battery, reduce the heat generation of the battery under high-rate working conditions, limit the area of the empty foil area on the positive electrode sheet 121 and the negative electrode sheet 125, and avoid the excessively high proportion of the empty foil area, which will increase the weight and volume of non-energy storage materials and affect the weight energy density and volume energy density of the lithium-ion battery 1.
[0066] Further, see Figure 3, at least one edge of the positive electrode active material layer 1210 is coated with an inorganic ceramic coating 1214, and the width of the inorganic ceramic coating 1214 is 1.1%-6.5% of the width of the positive electrode sheet 121. Preferably, the inorganic ceramic coating 1214 is coated on one side of the positive electrode active material layer 1210 close to the positive electrode empty foil area 1212 and extends to the positive electrode empty foil area 1212 to prevent the burrs generated when the positive electrode empty foil area 1212 is cut to form the positive electrode ear from piercing the diaphragm 123, causing a short circuit inside the battery. In addition, if the width of the inorganic ceramic coating 1214 is too wide, the width of the positive electrode active material layer 1210 will be reduced, thereby reducing the capacity of the winding core 12. The width of the inorganic ceramic coating 1214 is limited to 1.1%-6.5% of the width of the positive electrode sheet 121, which can not only improve the safety of the battery, but also minimize the impact on the battery capacity. The inorganic ceramic coating 1214 acts as a barrier to prevent the uncontrollable propagation of heat and current when an abnormal situation occurs in the battery, such as overcharging, over-discharging, short circuit, etc., thereby reducing the risk of thermal runaway; if the width of the inorganic ceramic coating 1214 is too wide, the width of the active material layer of the positive electrode sheet 121 will be reduced, thereby reducing the energy capacity of the core 12. The width of the inorganic ceramic coating 1214 is limited to 1.1%-6.5% of the width of the positive electrode sheet 121, which can not only improve the safety of the battery, but also minimize the impact on the battery capacity.
[0067] In some optional embodiments, the inorganic material particles forming the inorganic ceramic coating 1214 include one or more of aluminum oxide, manganese dioxide, magnesium oxide, silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, iron oxide, boehmite, gypsum, talc, and calcite, and the average particle size Dv50 of the inorganic material particles is 0.5-7.5 microns. The inorganic ceramic coating 1214 made of the above-mentioned inorganic material particles has good thermal stability, maintains electrical insulation in a high temperature environment, provides mechanical support for the positive electrode active material layer 1210, and enhances the structural stability of the positive electrode 121. The average particle size Dv50 of the inorganic material particles is 0.5-7.5 microns, which can form a more uniform coating and reduce coating pore defects. The coating quality and electrical insulation performance are good, which helps to improve the safety and cycle stability of the battery. It is understandable that if the size of the inorganic material particles is too large, the uniformity is poor, and the overall flatness and good fitting surface of the electrode cannot be guaranteed. The formed inorganic ceramic coating 1214 has poor adhesion and is easy to fall off; if the size of the inorganic material particles is too small, the inorganic ceramic coating 1214 is too dense, the electrode processing is difficult, and it is easy to lose powder.
[0068] In a specific implementation process, a method for manufacturing the diaphragm 123 is as follows:
[0069] A PE film with a thickness of 9 μm was used as a base film, and a ceramic coating and a polyvinylidene fluoride PVDF coating with a thickness of 1 μm were coated on both sides to form a diaphragm 123, and the air permeability of the diaphragm 123 was controlled to be ≥80s / 100mL.
[0070] The second aspect of the present application provides an electrical device, see Figure 5 , comprising a controller 2, a motor 3 connected to and controlled by the controller 2, and a battery for powering the controller 2, wherein the battery is a lithium-ion battery 1 according to any one of the above items. Since the lithium-ion battery 1 has the above-mentioned beneficial effects, the electrolyte system of the electrical device provided by the present application is more stable during high-power charging and discharging, and can inhibit the occurrence of thermal decomposition and side reactions, thereby improving the safety of use.
[0071] The electrolyte formula of the following examples is abbreviated as: H wt% lithium hexafluorophosphate + Iwt% fluoroethylene carbonate + Jwt% solvent (ethylene carbonate + diethyl carbonate + ethyl acetate) + K wt% additive (vinylene carbonate + lithium difluorophosphate + nitrile organic compound)
[0072] The technical solution of the present application is described below in conjunction with Examples 1-12 and Comparative Examples 1-4.
[0073]
[0074] The above-mentioned Examples 1-12 and Comparative Examples 1-5 were subjected to 600 cycles of cycle retention test, hot box test and 10C rate discharge temperature rise test respectively:
[0075] The test method for 600-cycle cycle retention rate is:
[0076] Take a lithium ion battery 1 prepared according to any of the above embodiments, place it in a constant temperature box at 25° C. for more than 4 hours, and test it according to the following steps:
[0077] S21: Charge the battery to 4.2V at a constant current at a 2C charge rate, and charge at a constant voltage to a current of 0.025C, and leave it for more than 15 minutes; discharge the battery to 2.5V at a 7.5C discharge rate, and record the discharge capacity as the initial capacity, denoted as a;
[0078] S22: repeat the above step S21 for 600 times; record the discharge capacity at the 600th cycle, denoted as b;
[0079] S23: Calculate the 600-cycle retention rate as b / a×100%.
[0080] The hot box test method is:
[0081] Take a lithium ion battery 1 prepared according to any of the above embodiments, place the battery in a 25° C. constant temperature box for more than 4 hours, and test it according to the following steps:
[0082] S31: The battery is discharged at a constant current of 0.1C discharge rate to 2.5V cut-off, and left to stand for 5 minutes;
[0083] S32: The battery is charged at a constant current of 0.2C to a cutoff of 4.2V, and at a constant voltage of 0.05C to a cutoff, and allowed to stand for 5 minutes;
[0084] S33: Place the battery in a heating box, set the heating rate to 5K / min, heat to 130°C, and keep it for 1 hour, then stop heating and cool it to below 30°C by self-heating;
[0085] S34: If the battery does not catch fire or emit smoke, it is considered to have passed; otherwise, it is considered to have failed. At least 6 batteries are tested in parallel for one embodiment or comparative example, and the pass rate is recorded.
[0086] 10C discharge rate temperature rise measurement method:
[0087] Take a lithium ion battery prepared according to any of the above embodiments, place the battery in a 25°C constant temperature box for more than 4 hours, and test it according to the following steps:
[0088] S41: At 25°C, charge the battery to 4.2V at a 1C charge rate, then charge at a constant voltage until the current is less than or equal to 0.05C, and let it stand for 30 minutes;
[0089] S42: Discharge the battery to 2.5V at a discharge rate of 10C, test the battery surface temperature T, and calculate the battery temperature rise to be: (T-25)°C.
[0090] Examples 1-3 and Comparative Examples 1 and 5 are based on the intensity ratio of characteristic absorption peaks A and B. A / I B The control group is a variable, and Examples 4-6 and Comparative Example 2 are based on the intensity ratio of characteristic absorption peaks C and D. C / I D The control group is a variable, Examples 7-9 and Comparative Example 3 are control groups with the material gram capacity of the positive electrode active material layer as a variable, and specific Examples 10-12 and Comparative Example 4 are control groups with the thickness of the fluorine-containing layer on the surface of the positive electrode active material layer and the ratio of the fluorine element content on the surface of the negative electrode active material layer d / x as a variable. The specific comparison results are shown in Tables 1-4:
[0091] Table 1
[0092] 600 cycles retention rate (%) 10C discharge temperature rise (℃) Hot box test pass rate Example 1 79.90 40.1 5 / 5 Example 2 85.10 40.4 5 / 5 Example 3 87.20 41.2 5 / 5 Comparative Example 1 62.70 51.2 0 / 5 Comparative Example 5 69.80 38.5 4 / 5
[0093] It can be seen from Table 1 that IA / I B The ratio of I A / I B When the ratio is too large, the probability of thermal decomposition of the electrolyte 13 is very high, so that in the 600-cycle test, the retention rate is not high, which shows that the battery capacity decays seriously, and the service life and safety cannot be guaranteed. A / I B When the ratio is very low, the discharge temperature rise of electrolyte 13 is small, indicating that the polarization of the battery has improved, but at this time the stability of electrolyte 13 is poor, there are too many side reactions, and the cycle retention rate is also poor. A / I B The best ratio is around 10%.
[0094] Table 2
[0095] 600 cycles retention rate (%) 10C discharge temperature rise (℃) Hot box test pass rate Example 4 86.60 40.6 5 / 5 Example 5 87.10 40.3 5 / 5 Example 6 87.90 40.5 5 / 5 Comparative Example 2 48.30 45.5 3 / 5
[0096] It can be seen from Table 2 that I C / I D The ratio of I A / I B The ratio of has a smaller effect on the temperature rise of the battery during discharge, but the heating of the battery is still aggravated, and the probability of thermal decomposition of the electrolyte 13 is also very high. In the 600-cycle test, I C / I D The ratio of I A / I B The ratio of has a greater impact on the battery capacity decay, which shows that the battery capacity decay is serious, which indirectly confirms that the battery chemical system is seriously damaged by the by-products of the electrolyte 13, and the battery life and safety cannot be guaranteed. C / I D The best ratio is around 40%.
[0097] Table 3
[0098]
[0099]
[0100] It can be seen from Table 3 that the higher the value of the material gram capacity E of the positive electrode active material layer 1210, the stronger the electrochemical activity of the positive electrode sheet 121, and at the same time, it may induce the electrolyte 13 to more easily undergo side reactions at the interface of the positive electrode sheet 121, resulting in a larger temperature rise of the battery, which will further induce thermal decomposition of the electrolyte 13, affecting the stability of the battery material structure, and making it easy to short-circuit and expand and crack the shell, which is consistent with the results of the hot box test, and the battery safety is poor. Among them, the value of the material gram capacity E is best at around 7mAh / g.
[0101] Table 4
[0102] 600 cycles retention rate (%) 10C discharge temperature rise (℃) Hot box test pass rate Example 10 79.60 42.5 4 / 5 Embodiment 11 76.30 42.6 3 / 5 Example 12 70.50 43.3 3 / 5 Comparative Example 4 56.70 46.8 0 / 5
[0103] It can be seen from Table 4 that the ratio of the thickness of the fluorine-containing layer on the surface of the positive electrode active material layer 1210 to the ratio of the fluorine content on the surface of the negative electrode active material layer 1250 to the proportion x, d / x, can significantly affect the cycle retention rate of the battery, wherein the larger the x, the more fluorine-containing substances in the electrolyte 13 system are deposited on the surface of the negative electrode sheet 125, and the larger the d, the more fluorine-containing substances in the electrolyte 13 system are deposited on the surface of the positive electrode active material layer 1210. Theoretically, the larger the values of x and d, the more stable the SEI film and the CEI film, which is beneficial for inhibiting the side reactions of the electrolyte. However, in actual implementation, the thickness d of the SEI film cannot be increased indefinitely. Therefore, d / x will also have an optimal value. Combined with the above embodiments, the optimal value of d / x is about 0.002.
[0104] In summary, the present application, on the one hand, can obtain the cycle performance and safety performance under high-rate charging or discharging conditions by improving the composition of the electrolyte 13 of the lithium-ion battery 1 and limiting the parameters of the specific characteristic absorption peaks in the infrared spectrum test, reduce the heating phenomenon of the battery, and delay the battery capacity decay. On the other hand, the improvement of the battery material system ensures the charging performance of the battery in the high-voltage state, as well as the improvement of the capacity upper limit and the high-rate input and output support of the battery.
[0105] In the description of this specification, reference to the terms "some embodiments", "an example", or similar descriptions means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment are included in at least one embodiment or example. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0106] Although examples of the present embodiment have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present embodiment, and the scope of the present embodiment is defined by the claims and their equivalents.
Claims
1. A lithium-ion battery, comprising a shell, a winding core assembled in the shell, and an electrolyte injected into the shell to infiltrate the winding core, the winding core comprising a positive electrode sheet, a separator, and a negative electrode sheet stacked in layers, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector, characterized in that: The electrolyte comprises: 12wt%-18wt% LiPF6, 3wt%-6wt% fluoroethylene carbonate, 0.1wt%-0.5wt% vinylene carbonate, 0.5wt%-1.5wt% lithium difluorophosphate and 0.4wt%-0.8wt% cyano-containing nitrile organic compound, and the balance is solvent; wherein the total weight percentage of the nitrile organic compound and the lithium difluorophosphate should be 1wt%-2wt%, and after Fourier transform infrared spectroscopy testing, it meets the following requirements: 5% ≤ I A / I B ≤25% and 25%≤I C / I D ≤ 50% Among them I A and I B They are 875-885cm in the infrared spectrum. -1 Wave number and 835~845cm -1 The intensity of the characteristic absorption peak centered at the wave number; I C and I D The infrared spectrum is 725-735 cm -1 Wave number and 710~720cm -1 The intensity of the characteristic absorption peak centered at wavenumber.
2. The lithium-ion battery according to claim 1, characterized in that The positive electrode sheet is a low residual alkali positive electrode sheet that has been washed with water, and the electrolyte needs to be discharged by the battery at least once to the discharge cut-off voltage, and then tested by Fourier transform infrared spectroscopy.
3. The lithium-ion battery according to claim 2, characterized in that: The Fourier transform infrared spectroscopy test comprises the following steps: S11: Take one of the lithium-ion batteries and let it stand at 25° C. for 4 hours; S12: discharging the lithium-ion battery at a discharge rate less than or equal to 0.2C until the cut-off voltage is reached, and leaving the battery to stand for 30 minutes; S13: disassembling the lithium-ion battery and extracting the electrolyte by centrifugation; and S14: The electrolyte is transferred to a closed liquid pool and then sent to a Fourier transform infrared spectrometer for testing. The infrared absorption spectrum wavelength range is set to: 400 cm -1 -4000cm -1 , scan to obtain an infrared spectrum containing several characteristic absorption peaks.
4. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The conductivity of the electrolyte at 25° C. is greater than or equal to 10 mS / cm, and the lithium ion transference number is greater than or equal to 0.
4.
5. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The lithium-ion battery is charged at a rate of 0.1C at 25°C. When the battery voltage is charged to a range of 4.45V-4.78V, the material gram capacity of the positive electrode active material layer is E mAh / g, and 5≤E≤20.
6. The lithium ion battery according to any one of claims 1 to 3, characterized in that: After the lithium-ion battery completes 100 charge and discharge cycles, the thickness of the fluorine-containing layer on the surface of the positive electrode active material layer is measured to be d micrometers. The DES energy spectrum is used for micro-area element analysis. The proportion of the fluorine content on the surface of the negative electrode active material layer to all elements is x%, satisfying: <d / x<0.1。 7. The lithium-ion battery according to claim 1, characterized in that: The solvent includes one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, and the nitrile organic compound is succinonitrile and / or 1,3,6-hexanetrinitrile.
8. The lithium-ion battery according to claim 1, characterized in that The positive electrode active material layer comprises a positive electrode active material, a positive electrode binder and a positive electrode conductor. The positive electrode active material is a metal oxide formed by a composite of one or more metal elements selected from cobalt, manganese, aluminum and nickel and lithium.
9. The lithium-ion battery according to claim 8, characterized in that: The negative electrode active material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductor. The negative electrode active material includes one or more of artificial graphite, natural graphite, silicon-oxygen material and silicon-carbon material. The mass proportion of silicon in the negative electrode active material is 0%-22%.
10. The lithium ion battery according to claim 8, characterized in that The positive electrode active material is lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, and the ratio of nickel atoms in the positive electrode active material to the total number of transition metal atoms is greater than or equal to 79%.
11. The lithium ion battery according to claim 9, characterized in that: A positive electrode empty foil area not covered by the positive electrode active material layer is reserved on the positive electrode collector, and the positive electrode empty foil area accounts for 1.8%-12.5% of the surface area of the positive electrode collector; a negative electrode empty foil area not covered by the negative electrode active material layer is reserved on the negative electrode collector, and the negative electrode empty foil area accounts for 1.5%-12% of the surface area of the negative electrode collector.
12. The lithium ion battery according to claim 8, characterized in that At least one edge of the positive electrode active material layer is coated with an inorganic ceramic coating, and the width of the inorganic ceramic coating is 1.1%-6.5% of the width of the positive electrode sheet.
13. The lithium ion battery according to claim 12, characterized in that: The inorganic material particles forming the inorganic ceramic coating include one or more of aluminum oxide, manganese dioxide, magnesium oxide, silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, iron oxide, boehmite, gypsum, talc, and calcite, and the average particle size Dv50 of the inorganic material particles is 0.5-7.5 microns.
14. An electrical device, characterized in that: It comprises a controller, a motor connected to and controlled by the controller, and a battery for supplying power to the controller, wherein the battery is a lithium-ion battery according to any one of claims 1 to 13.